Analysis of the Implementation of the SAP (Safety Accountability Program) Digital Reporting Application in Reducing Workplace Accidents at the PT Energi Batubara Lestari Coal Mine - Arief Aminuddin; Nine Elissa Maharani; Nur Ani; Wartini Wartini (Publikasi Indonesia, 2025)
This study aims to evaluate the effectiveness of the digital SAP application in reducing workplace accidents in a coal mining company in South Kalimantan. The research method employed a descriptive quantitative case study approach, involving 150 respondents from various departments. Data were collected through accident documentation over a 12-month period (6 months before and 6 months after implementation of the application), questionnaires, interviews, and field observations. Data analysis was carried out using descriptive comparisons and paired t-tests to examine the significance of accident reduction. The results show a 75% decrease in workplace accidents after the application was implemented. The number of SAP reports in 2025 was consistently higher compared to 2024, with a significant difference of around 2.000–3.000 reports per month, reflecting a more consistent reporting culture. This indicates system improvement and increased worker participation following the full implementation of the digital SAP application in 2025. Surveys revealed that 85% of respondents found the application easy to use, 78% stated it encouraged them to be more proactive in maintaining safety, 75% reported an improved safety culture, and 85% felt the application helped reduce potential hazards. In conclusion, the digital SAP application has proven effective in strengthening the OSH reporting system, increasing worker participation, accelerating follow-up actions, and significantly reducing workplace accidents. This study recommends the broader adoption of the digital SAP application in the mining industry as part of a strategy towards a proactive and sustainable safety culture.